Rewiring of primary metabolism for ammonium recycling under short-term low CO2 treatment – its implication for C4 evolution - Miao, Fenfen; Wang, Ying; Haq, Noor UI; Lyu, Ming-Ju Amy; Zhu, Xin-Guang (Frontiers in Plant Science, 2024)
Low CO2 is recognized as a major environmental condition under which C4 photosynthesis evolved. So far, most researchers thought that low CO2 acts mainly as a screening condition, under which plants with relatively low CO2 compensation point can gain competitive advantage. In this study, combining physiology, transcriptomics, and metabolomics data, we provide evidences that low CO2 also induce a change in the expression of genes related to C4 metabolism, hence providing a direct linkage between low CO2 as a signaling mechanism during the evolution of C4 photosynthesis. In nature conditions inducing low physiological CO2 levels such as drought and high temperature etc are widespread, therefore, regulation of genes related to C4 photosynthesis via physiological low CO2 might participate in plant acclimation under stresses.